Body talk on social networking sites and appearance anxiety among college students: the mediating role of self-objectification and moderating role of gender - Ruan, Jiayi; Yu, Ruicong; Zhao, Yunfeng; Xie, Lunfang; Mei, Yaqi (Frontiers in Psychology, 2025)
IntroductionAlthough the factors influencing appearance anxiety have been explored, the correlation and underlying mechanisms of action between social media body talk and appearance anxiety remain unclear. This study proposes research hypotheses and conducts mutual validation of scale data and real media data to explore the mechanism of action between variables.MethodsA mixed-methods design was employed: 512 college students completed questionnaires containing the Appearance Conversations with Friends Scale, the Appearance Anxiety Scale–Brief Version, and the Body Surveillance Subscale of the Objectified Body Consciousness Scale. Furthermore, 1,011 actual social media data entries were analyzed to complement the empirical framework.ResultsThe results showed that college students’ body talk on social networking sites, appearance anxiety, and self-objectification were significantly positively correlated. Body talk on social networking sites had a significant positive predictive effect on appearance anxiety, with self-objectification having a partial mediating effect. Gender played a significant moderating role between social media body talk and appearance anxiety (β = 0.53, p < 0.01), with male students’ social media body talk positively predicting appearance anxiety more significantly than female students (β = 0.52, p < 0.05).DiscussionThese results extend objectification theory by demonstrating how technology-mediated body talk amplifies appearance anxiety through self-surveillance behaviors. These findings may be helpful for developing targeted interventions to reduce the risk of appearance anxiety among college students who often talk about their appearance on social networking sites.